The Benefit of Islamic Faith Education to Enhance Children Social and Emotional Skills - Nuri Sadida; Arif Triman (Jurnal Pendidikan Islam, 2018)
There is an increasing trend among parents nowadays to choose Islamic elementary school. This has triggered the increasing amount of schools that adopt religious bases such as Kuttab Al-Fatih (KAF), a school that emphasized manner education and Islamic faith teaching. The purposes of this study are to correlate Islamic faith education given by parents and student’s social and emotional skills and to compare children's emotional and social skills from parents whose children schooled in KAF and in other schools. The measurement of children's social and emotional skills contains three dimensions: persistence, self-control, and social competence. Meanwhile, faith education by parents was measured using how much parents teach faith indicator. There are 52 parents participated in this study. Results showed there is a significant correlation between faith education and social and emotional skills (r=.302, p < .05), and there is no significant difference in social and emotional skills between children who submitted to KAF and to other schools.